(untitled) (Journal of actual problems of jurisprudence, 2018)
Questions of formation of legal culture of migrants in Kazakhstan are more than ever. Migrants are different from the values of the local popula¬tion, landmarks, faith, rules of behavior, communication style, often have a particular family structure and hierarchy of relationships within society. Unfortunately, migration processes are now a factor in the deterioration of the crime situation. This is due to ignorance of the laws of migrants, inconsistency of legal culture and an adequate level of legal consciousness. In order to improve the legal culture of migrants, it is necessary to implement a set of measures on legal education, legal education and legal education of migrants. Key words: law culture of migrants, migration processes in Kazakhstan, Law consciousness, Law education, Law education of migrants.